Retrievals of Aerosol Optical Depth and Spectral Absorption From DSCOVR EPIC - Lyapustin, Alexei; Go, Sujung; Korkin, Sergey; Wang, Yujie; Torres, Omar; Jethva, Hiren; Marshak, Alexander (Frontiers in Remote Sensing, 2021)
A new algorithm is described for joint retrievals of the aerosol optical depth and spectral absorption from EPIC observations in the UV – Vis spectral range. The retrievals are illustrated on examples of the wildfire smoke events over North America, and dust storms over greater Sahara region in 2018. An initial evaluation of single scattering albedo (SSA) at 443 nm over these regions shows a good agreement with AERONET data, generally within the uncertainty of AERONET SSA of ±0.03. A particularly good agreement is achieved for dust with R~0.62, rmse~0.02, negligible bias, and 85% points within the expected error. This new capability is part of version 2 MAIAC EPIC algorithm. The v2 algorithm has recently completed reprocessing of the EPIC record covering the period of 2015-2020.